Il romanzo di Elena in Achille Tazio: reminiscenze tragiche - Greta Castrucci (Parole Rubate, 2018)
Permeated by classical echoes, Achilles Tatius’novel lends itself well to an incorporation of varied and precise references to a fictional and atypical tragedy such as Euripides’ Helen. Through an analysis of the recognisable allusions in the main storyline, including Leucippe and Clitophon’s journey, which draws upon Helen and Menelaus’ escape, but also in secondary stories such as Melite’s, this article aims to investigate the recurring fictional reinterpretations of Euripidean motifs that make Helena new ethical exemplum, reworked and adapted to a different literary, historical, and cultural context.